Fuzzy Adaptive Fault-Tolerant Stability Control Against Novel Actuator Faults and Its Application to Mechanical Systems - Shen, Qikun; Shi, Peng; Lim, Chee Peng (IEEE transactions on fuzzy systems, 2024)
This article studies the stability control problem of uncertain nonlinear systems with unknown multiple classes of actuator faults. We investigate not only traditional actuator gain and bias faults but also a class of novel actuator faults, i.e., input power faults , which are induced by the change of system input powers. By combining fuzzy logic systems, adaptive control, and other control technologies and methods, we develop an adaptive fault-tolerant fuzzy control scheme that guarantees that the system under scrutiny is asymptotically stable and the system states asymptotically converge to an adjustable small neighborhood of the origin. Compared with the existing results, input power faults, as a class of novel actuator faults, are first proposed and investigated in this article, and the corresponding fault-tolerant control scheme is studied. Furthermore, even if the system is subject to unknown input power faults, the actuator faults, especially bias faults, can be compensated properly. Based on a mechanical system, the simulation results indicate the effectiveness of our proposed fault-tolerant control method.